Comparative Effectiveness of Angiotensin-Converting Enzyme Inhibitor-Based Treatment on Cardiovascular Outcomes in Hypertensive Blacks versus Whites - Ogedegbe, Gbenga (J Am Coll Cardiol, 2015)
BACKGROUND: Clinical trial evidence suggests poorer outcomes in blacks compared to whites when treated with angiotensin-converting enzyme (ACE) inhibitor-based regimen, but this has not been evaluated in clinical practice. OBJECTIVES: We evaluated the comparative effectiveness of an ACE inhibitor-based regimen on a composite outcome of all-cause mortality, stroke, and acute myocardial infarction (AMI) in hypertensive blacks compared to whites. METHODS: We conducted a retrospective cohort study of 434,646 patients in a municipal health care system. Four exposure groups (Black-ACE, Black-NoACE, White-ACE, White-NoACE) were created based on race and treatment exposure (ACE or NoACE). Risk of the composite outcome and its components was compared across treatment groups and race using weighted Cox proportional hazard models. RESULTS: Our analysis included 59,316 new users of ACE inhibitors, 47% of whom were black. Baseline characteristics were comparable for all groups after inverse probability weighting adjustment. For the composite outcome, the race treatment interaction was significant (p = 0.04); ACE use in blacks was associated with poorer cardiovascular outcomes (ACE vs. NoACE: 8.69% vs. 7.74%; p = 0.05) but not in whites (6.40% vs. 6.74%; p = 0.37). Similarly, the Black-ACE group had higher rates of AMI (0.46% vs. 0.26%; p = 0.04), stroke (2.43% vs. 1.93%; p = 0.05) and chronic heart failure (3.75% vs. 2.25%; p < 0.0001) than the Black-NoACE group. However, the Black-ACE group was no more likely to develop adverse effects than the White-ACE group. CONCLUSIONS: ACE inhibitor-based therapy was associated with poorer cardiovascular outcomes in hypertensive blacks but not in whites. These findings confirm clinical trial evidence that hypertensive blacks have poorer outcomes than whites when treated with an ACE inhibitor-based regimen.